Canadian Semantic Web Technologies and Applications - Du, Weichang; Ensan, Faezeh; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The emergence of Web technologies for data and knowledge interaction gives rise to the need for supportive frameworks for knowledge distribution. Semantic Web technologies aim at providing shared semantic spacesfor Web contents, such that people, applications and communities can use a common platform to share information. Also, many of the challenging aspects of the research problems tackled in the Semantic Web area fall in the realm of artificial intelligence or employment of AI techniques. Canadian Semantic Web: Technologies and Applications is an edited volume contributed by worldwide leaders in Semantic Web research, and was based on the May 2009, Canadian Semantic Web Symposium, Kelowna, BC. This volume will introduce the most advanced working theories, prototypes and applications on; AI technologies in the Semantic Web, Languages, tools and methodologies for the Semantic Web, Searching, querying, visualizing and interpreting the Semantic Web, Semantic Web-based Knowledge Management, Semantic Grid and semantic Grid services, Trust, privacy, security on the Semantic Web and more. A special focus on applications of semantic web technology on electronic health. About this book: Introduces the most advanced working theories, prototypes and applications. Provides a special focus on applications of semantic web technology on electronic health. This book is intended for practitioners and researchers working in the related fields of the Semantic Web. Advanced-level focusing on computer science will also find this book valuable as a secondary text or reference book.
Incremental Query Rewriting with Resolution -- Knowledge Representation and Reasoning in Norm-Parameterized Fuzzy Description Logics -- A Generic Evaluation Model for Semantic Web Services -- A Modular Approach to Scalable Ontology Development -- Corporate Semantic Web: Towards the Deployment of Semantic Technologies in Enterprises -- Semantic Service Matchmaking in the ATM Domain Considering Infrastructure Capability Constraints -- Developing Knowledge Representation in Emergency Medical Assistance by Using Semantic Web Techniques -- Semantically Enriching the Search System of a Music Digital Library -- Application of an Intelligent System Framework and the Semantic Web for the CO2 Capture Process -- Information Pre-Processing using Domain Meta-Ontology and Rule Learning System.
Keywords: Computer science; Information systems; Information storage and retrieval systems; Artificial intelligence; Text processing (Computer science; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Models and Principles; Information Systems and Communication Service; Document Preparation and Text Processing